Effect of Low Lactose Formula on the Short-Term Outcomes of Neonatal Abstinence Syndrome: A Systematic Review - Mahdi Alsaleem MD; Jarrod Dusin MS, RD, LD, CPHQ; Gangaram Akangire MD, MS, FAAP (SAGE Publishing, 2021)
The use of low lactose formula (LLF) in term and near-term infants in infants with neonatal abstinence syndrome (NAS) has been increasing recently. However, the clinical evidence of such use is limited. Our aim in this paper was to systematically review the current literature about the use of LLF in infants with NAS. We searched PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, and Cochrane Database of Systematic Reviews for articles published between 2015 and 2020. Only randomized controlled trials, prospective, and retrospective studies. The risk of bias was assessed by using published tools appropriate for the study type. The certainty of the evidence was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Forty-one titles and/or abstracts were screened independently by 2 reviewers (MA and GA). After an indepth review, 4 studies answered the study question (1 randomized controlled trial (RCT), 2 retrospective studies, and 1 quality improvement study). A meta-analysis could not be completed due to the study type difference and how the outcomes were reported. The studies found no benefit to feeding LLF to infants with NAS regarding short-term outcomes (length of stay, duration, and need for pharmacological therapy and growth). Certainty in the evidence is low. In conclusion we found no beneficial effects regarding the need for pharmacological therapy, duration of pharmacological treatment, length of hospital stay, and growth of using LLF compared to the standard formula in infants with NAS.